2014
DOI: 10.1371/journal.pone.0104456
|View full text |Cite
|
Sign up to set email alerts
|

Mating Damages the Cuticle of C. elegans Hermaphrodites

Abstract: Lifespan costs to reproduction are common across multiple species, and such costs could potentially arise through a number of mechanisms. In the nematode Caenorhabditis elegans, it has been suggested that part of the lifespan cost to hermaphrodites from mating results from physical damage owing to the act of copulation itself. Here, we examine whether mating damages the surface of the hermaphrodite cuticle via scanning electron microscopy. It is found that mated hermaphrodites suffered delamination of cuticle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Male sperm and seminal fluid also trigger physiological changes in mated hermaphrodites (38). It also has been shown that the act of mating is followed by the appearance of cuticular damage around the hermaphrodite vulva (39). Unfortunately, whether any of these physiological and lifespan alterations are detrimental to hermaphrodite fecundity or the fitness of their offspring is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Male sperm and seminal fluid also trigger physiological changes in mated hermaphrodites (38). It also has been shown that the act of mating is followed by the appearance of cuticular damage around the hermaphrodite vulva (39). Unfortunately, whether any of these physiological and lifespan alterations are detrimental to hermaphrodite fecundity or the fitness of their offspring is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these changes are body fragility/shrinkage, reduced osmotic stress resistance, and general behavioral decrepitude. Why excessive male secretions deleteriously alter the hermaphrodite is not known, but this is speculated to be either a form of male-directed population control or sexual conflict to limit the outcrossed hermaphrodite from further copulation (Maures et al 2014;Shi and Murphy 2014;Ting et al 2014;Woodruff et al 2014;Palopoli et al 2015).…”
Section: Physiology and Behavior: Sex-specific And Sexually Modulatedmentioning
confidence: 99%
“…Sexual conflict in Caenorhabditis also may involve maleinduced harm to females. Male spicules scrape and physically damage the hermaphrodite cuticle in the vicinity of the vulva [73], and mating reduces her lifespan owing in part to physiological changes induced by sensing the chemical secretions of males [74][75][76]. The mating structure of males provides one of the most conspicuous and rapidly evolving morphological traits in Caenorhabditis [5], as in many other organisms [69], implicating selection of some form in its evolution.…”
Section: How Intense Are Sexual Selection and Sexual Conflict In Nature?mentioning
confidence: 99%